2020
DOI: 10.1016/j.cegh.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Mobile addiction and its relationship with quality of life in medical students

Abstract: Background: Quality of life is one of the most important health-related outcomes that can be affected by mobile phone addiction. This study was conducted to determine the prevalence of mobile phone addiction and its relationship with quality of life in students of Birjand University of Medical Sciences (BUMS). Methods: This cross-sectional study was conducted on 360 students in BUMS in 2018. The sample was randomly selected from each faculty using proportional stratified sampling. To collect data, a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…It has been found that MS3 is positively BOLD related to the fronto-insular SN, including the dACC, the bilateral inferior frontal cortex, and the insula ( Fox et al, 2006 ; Seeley et al, 2007 ), which play a critical role in switching between central executive function and the default mode ( Sridharan et al, 2008 ). The experiments of Miri et al (2019) showed that the physical and psychological effects of excessive cell phone use include headaches and memory loss, and the brain regions involved in the default mode network (MS3) include the hippocampus, which explains why memory loss occurs in addicts. From the above evidence, we may infer that the addict’s insula activity increases, leading to withdrawal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that MS3 is positively BOLD related to the fronto-insular SN, including the dACC, the bilateral inferior frontal cortex, and the insula ( Fox et al, 2006 ; Seeley et al, 2007 ), which play a critical role in switching between central executive function and the default mode ( Sridharan et al, 2008 ). The experiments of Miri et al (2019) showed that the physical and psychological effects of excessive cell phone use include headaches and memory loss, and the brain regions involved in the default mode network (MS3) include the hippocampus, which explains why memory loss occurs in addicts. From the above evidence, we may infer that the addict’s insula activity increases, leading to withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Jacobsen and Forste (2011) identified a significant negative association between the use of mobile phones and academic performance among first-year university students in the United States. MPA has become a global concern because of its negative effects on memory and interpersonal communication ( Hao et al, 2019 ; Miri et al, 2019 ), as well as its association with negative emotions (anxiety, depression, stress, and loneliness) ( Demirci et al, 2015 ; Chen et al, 2016 ; Gao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is aligned with Zyngier's (2008) argument that youth development can be strengthened during the learning process if they are given the opportunity to develop and explore any kind of prospects that are not confined to the prestructured education system. However, discussions about the development of research self-efficacy or self-efficacy among postgraduates frequently centre on the doctoral level, adult age level, field of psychology or counselling, self-efficacy and the work profession, and field of medicine or nursing (as example through research; (Rowe-Johnson, 2018;Speer et al, 2021;Miri et al, 2018;Nazari et al, 2021). Yet, there is currently a paucity of study and in-depth material that focuses on how postgraduate degrees, such as Master's and Doctor of Philosophy programmes, assist youth enhance their sense of self-efficacy.…”
Section: Application Of Extension Education Principles In Formal Settingmentioning
confidence: 99%
“…Buctot and colleagues [17] also showed, using KID-SCREEN-27, that PSU is negatively correlated with several domains (physical health and psychological health, school environment) but unrelated to others (e.g., autonomy, parental, and peer support). Another study that used the SF-12 showed that PSU is associated with poor mental health but not physical health [69].…”
Section: Relationships Between Psu and Qol Or Hrqolmentioning
confidence: 99%